1999
DOI: 10.1038/sj.bjc.6690701
|View full text |Cite
|
Sign up to set email alerts
|

The distinct role of CD4+ and CD8+ T-cells during the anti-tumour effects of targeted superantigens

Abstract: Summary To target T-cells to the tumour area we created a recombinant protein of the bacterial superantigen (SAg) Staphylococcal enterotoxin A (SEA) and the Fab-fragment of a tumour-reactive antibody. This antibody-targeted SAg immunotherapy therapy has been shown to be highly efficient, eliminating > 95% of the pulmonary metastasis in mice carrying established melanoma micrometastases. Earlier studies demonstrated that elimination of the C215-expressing B16-melanoma lung metastasis was dependent on interferon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Because our previously published studies show that anti-class II Abs can completely abrogate T cell-mediated autologous monocyte cytotoxicity and anti-class I was less effective (9), we propose that CD4 ϩ T cells are required for the killing, although CD8 ϩ T cells may play an additional role, since CD4 ϩ T cells alone kill less efficiently than unfractionated T cells. The importance of a finely tuned cellular collaboration between CD4 ϩ and CD8 ϩ T cells for cytotoxicity has been described by other groups (32)(33)(34). We had previously shown that this phenomenon is specific for autologous monocytes, since SLE T cells do not kill allogeneic monocytes from normal or other lupus patients, and the killing was inhibited with mAbs to class II MHC determinants (9).…”
Section: Discussionmentioning
confidence: 90%
“…Because our previously published studies show that anti-class II Abs can completely abrogate T cell-mediated autologous monocyte cytotoxicity and anti-class I was less effective (9), we propose that CD4 ϩ T cells are required for the killing, although CD8 ϩ T cells may play an additional role, since CD4 ϩ T cells alone kill less efficiently than unfractionated T cells. The importance of a finely tuned cellular collaboration between CD4 ϩ and CD8 ϩ T cells for cytotoxicity has been described by other groups (32)(33)(34). We had previously shown that this phenomenon is specific for autologous monocytes, since SLE T cells do not kill allogeneic monocytes from normal or other lupus patients, and the killing was inhibited with mAbs to class II MHC determinants (9).…”
Section: Discussionmentioning
confidence: 90%
“…44 In addition, it was recently demonstrated that T cell receptor triggering in the presence of IL-10 inhibited IFN-␥ production in freshly isolated CD4 + T cells 45 and downregulated the expression of granzyme B. 40,46 The production of IL-4 in the tumor-bearing C57BL/6 mice treated with C215Fab-SEA alone increased as compared with that of mice in control groups, while the level of IL-4 in mice treated with AdIL-18 alone was lower that in mice of control groups. After the combined treatment with C215Fab-SEA/Ad IL-18, the IL-4 level of tumorbearing C57BL/6 mice decreased as compared with that in mice treated with C215Fab-SEA alone.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to suppress both IFN-␥ production and the antitumor effector phase of IFN-␥. [39][40][41] It may inhibit and down-regulate MHC-II molecule expression of monocytes as well as interfere with antigen presentation, 42 inhibit the up-regulation of co-stimulatory molecules 43 and suppress the cytotoxicity of macrophages. 44 In addition, it was recently demonstrated that T cell receptor triggering in the presence of IL-10 inhibited IFN-␥ production in freshly isolated CD4 + T cells 45 and downregulated the expression of granzyme B.…”
Section: Discussionmentioning
confidence: 99%
“…Activation leads to the expression of perforin and the production of cytotoxic and proinflammatory cytokines and thus death of the APC (Fischer et al, 1990;Dohlsten et al, 1991b). Targeting of superantigens towards tumours induces a strong, local cytotoxic T-cell attack, which directly kills tumour cells and leads to inflammation and the local accumulation of tumouricidal cytokines (Dohlsten et al, 1991a(Dohlsten et al, , 1994(Dohlsten et al, , 1995Litton et al, 1997Litton et al, ,1999.…”
mentioning
confidence: 99%